2014
DOI: 10.3109/17435390.2014.940405
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila melanogasteras a model organism to study nanotoxicity

Abstract: Drosophila melanogaster has been used as an in vivo model organism for the study of genetics and development since 100 years ago. Recently, the fruit fly Drosophila was also developed as an in vivo model organism for toxicology studies, in particular, the field of nanotoxicity. The incorporation of nanomaterials into consumer and biomedical products is a cause for concern as nanomaterials are often associated with toxicity in many in vitro studies. In vivo animal studies of the toxicity of nanomaterials with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(59 citation statements)
references
References 85 publications
0
51
0
2
Order By: Relevance
“…38 Since our in vitro studies using the human lung MRC5 cells showed that ZnO NP exposure can trigger cell death, we decided to confirm this finding using Drosophila as an in vivo model organism. Adult flies were fed ZnO NPs at a wide variety of concentrations by the ingestion.…”
Section: Larval Uptake Of Nps In the Fruit Fly Drosophilamentioning
confidence: 97%
See 1 more Smart Citation
“…38 Since our in vitro studies using the human lung MRC5 cells showed that ZnO NP exposure can trigger cell death, we decided to confirm this finding using Drosophila as an in vivo model organism. Adult flies were fed ZnO NPs at a wide variety of concentrations by the ingestion.…”
Section: Larval Uptake Of Nps In the Fruit Fly Drosophilamentioning
confidence: 97%
“…Drosophila shows high levels of physiological similarity and gene conservation to humans. 38,62,63 In addition, the signaling pathways that control developmental processes are highly conserved between Drosophila and mammals, making it a suitable and promising in vivo model for elucidating the detailed molecular mechanisms of NP-mediated toxicity. 64 It was previously reported that there is no toxicity or oxidative stress induction observed in Drosophila larvae when exposed to ZnO NPs.…”
mentioning
confidence: 99%
“…Understanding the relative toxicities of different modes of nanoparticle exposure, as compared with their dissolved metal ions, are emerging areas in ecotoxicology (Jackson et al, 2012). In this context it must be remembered that Drosophila melanogaster as an in vivo organism has proved to be a qualified model in detecting potential harmful effects of nanomaterials (Pompa et al, 2011a(Pompa et al, ,2011bVecchio, 2014;Ong et al, 2015;Alaraby et al, 2014). In fact Drosophila has already been successfully used to detect the toxic effect of CdSe/ ZnS QDs (Galeone et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Although the invertebrates Drosophila melanogaster and Caenorhabditis elegans are used in experiments in general biology, injection of a precise volume of a sample to determine the LD 50 in pharmacological analyses is difficult because invertebrates have small bodies (9,10). The silkworm has been proposed as an invertebrate model in which to quantitatively administer a drug solution via injection with a typical syringe (11,12).…”
Section: Introductionmentioning
confidence: 99%